Quality of life 1 year after hospital discharge in unvaccinated pregnant women with COVID-19 respiratory symptoms: a prospective observational study (ODISSEA-PINK study) - Vetrugno, Luigi; Sala, Alessia; Deana, Cristian; Meroi, Francesco; Grandesso, Maria; Maggiore, Salvatore Maurizio; Isola, Miriam; De Martino, Maria; Restaino, Stefano; Vizzielli, Giuseppe; Bove, Tiziana; Driul, Lorenza (Frontiers in Medicine, 2023)
Little is known about Quality of Life within the first court of unvaccinated COVID-19 pregnant women exposed to the pandemic stressor. Primary aim of this study was to evaluate 1 year after hospital discharge HRQoL in a cohort of COVID-19 unvaccinated pregnant patients with COVID-19. Methods: in this prospective observational study, all COVID-19 positive pregnant women at any gestational age, admitted to the Obstetric Department at the University Hospital of Udine, Italy, from March 1, 2020, to March 1, 2021, requiring or not oxygen supplementation due to SARS-CoV2 pneumonia were evaluated. Patients with a history of neurological or psychiatric disease, those with a previous abortion, and those who refused to provide written informed consent were excluded from the study. We investigated pregnant positive COVID-19 women Health-related quality of life (HRQoL) with the Short-Form Health Survey-36 (SF-36) and Post-traumatic Stress-Disorder (PTSD) with the Impact of Event Scale-Revised (IES-R). Results: 62 pregnant women respected the inclusion criteria of the study, and data from 33 patients were analyzed. The mean age was 32±6 years, with a median gestational age of 38 weeks [IQR 34-40]. 15.2% of patients required oxygen therapy through noninvasive respiratory support (with high flow nasal cannula) for a median of 9 days [IQR 6-12]. The median Physical Component Summary (PCS) and Mental Component Summary (MCS) scores were 50.2 [IQR 46.7-53.7] and 56.0 [IQR 46.8-60.6] respectively. Ten patients out of 33 (30%) tested positive for PTSD. Maternal age, gestational age, and history of cardiac-pulmonary-kidney disease significantly affected HRQoL at multivariable analysis. Discussion: In COVID-19 pregnant unvaccinated women some physical impairments reducing HRQoL are still present one year after hospital discharge. Previous medical history such as history of cardiac-pulmonary-kidney disease significantly affected HRQoL. Long and repeated follow-up should be pursued in this category of patients. Trial Registration: ClinicalTrials.gov with the number NCT04860687.